A liberdade religiosa na Dignitatis Humanae: uma releitura a partir do Princípio de Cooperação - Coelho, Renato Arnellas (2024)
Religious liberty is a subject that is always underlying the historical problems of relationship between different forms of government and religious practice. Its importance is indisputable whether in the religious or civil domain. It is not a study only within the Catholic Church, but it is of universal relevance. The declaration Dignitatis Humanae appears as the most solemn expression of the recent Church about this issue, trying to help in understanding its fundamentals and, mainly, its practical use. The text of Dignitatis Humanae had a difficult formation, as it is also important to consider previous teachings of the Church on the same subject with which the declaration is linked and makes references to. However, due to time restraints and intrinsic difficulties of the communicative process, the final approved text of Dignitatis Humanae was not received equally among its readers. One can distinguish here three main types of approach to the text: one considering a positive rupture, one considering a negative rupture and one considering continuity regarding previous magisterial teaching. In order to help understand better each kind of approach, it is used as a theoretical tool Paul Grice‘s Principle of Cooperation. Through the usage of the Principle of Cooperation it is possible to see better the problems of each communicative process, as well as in which point it is needed to work more to diminsh possible failures in the mutual comprehension. After concluding the analysis of each approach, it is noticeable that the continuity approach helps better comprehending Dignitatis Humanae and can be used as a support for a new pronouncement from the Church that advances further the subject of religious liberty, not so much in the theoretical field, but mainly in its practical aspect that is so urgently needed for the for peaceful coexistence among men